2005
DOI: 10.1177/0310057x0503300606
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Re-usable LMA Classic and Two Single-use Laryngeal Masks (LMA Unique and SoftSeal) in Airway Management by Novice Personnel

Abstract: In a single-blind randomized trial, three types of laryngeal masks: the reusable LMA Classic™, the single-use LMA Unique™ and SoftSeal™ were inserted by novice medical officers in anaesthesia. Five successive attempts were undertaken with each mask type. The order of the mask type insertion was randomly selected. Mean (SD) insertion times for LMA Classic™, LMA Unique™ and Soft Seal™ were 32.9 (12.3), 39.6 (23.4) and 49.4 (50.4) seconds respectively. Differences were only significant between LMA Classic™ and So… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 26 publications
1
19
1
Order By: Relevance
“…However, this potential advantage had no clinical implication because it did not result in improved ventilation in this group and airway pressure was easily maintained below sealing pressure in all patients. Our results are in agreement with those of Paech et al [13], Tan et al [21], Cook et al [18], and Francksen et al [22], who reported a better airway seal with the Soft Seal than the LMA Unique. In contrast, Brimacombe et al [16] found no differences in leak pressure between the Soft Seal and the LMA Unique in paralyzed patients.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…However, this potential advantage had no clinical implication because it did not result in improved ventilation in this group and airway pressure was easily maintained below sealing pressure in all patients. Our results are in agreement with those of Paech et al [13], Tan et al [21], Cook et al [18], and Francksen et al [22], who reported a better airway seal with the Soft Seal than the LMA Unique. In contrast, Brimacombe et al [16] found no differences in leak pressure between the Soft Seal and the LMA Unique in paralyzed patients.…”
Section: Discussionsupporting
confidence: 93%
“…Although differences among studies in the definition of insertion time do not permit easy comparison, the longer insertion time in our study compared with that from other studies performed by expert users reflects more attempts and more time per attempt, as is to be expected from operators with little experience [20,21]. We found no significant differences in insertion time among the device groups, but the Ambu LM had the shortest insertion time, probably owing to its curved shape.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…LMAs are recommended by professionals for airway rescue in failed intubation [15]. Older models, such as the LMA-Classic Ò , LMA-ProSeal Ò , or Soft Seal have been shown to rescue the airway in a quick and safe fashion.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we compared the performance of the Supreme and the conventional Soft Seal Ò LMA (Smiths Medical, USA) during chest compression with a manikin [6].…”
Section: Introductionmentioning
confidence: 99%